Humanized mouse model reveals the immunogenicity of Hepatitis B Virus vaccine candidates produced in CRISPR/Cas9-edited Nicotiana benthamiana - Iuliana Caras; Irina-Elena Ionescu; Ana-Maria Pantazica; André van Eerde; Hege Steen; Inger Heldal; Sissel Haugslien; Catalin Tucureanu; Raluca-Elena Chelmus; Vlad-Constantin Tofan; Adriana Costache; Adrian Onu; et al. (Frontiers in Immunology)
IntroductionHepatitis B Virus (HBV) infection is still an ongoing public health issue worldwide. The most efficient tool in preventing HBV infection remains vaccination and significant efforts have been made in the last decade to improve current HBV vaccines. Owing to the strict HBV tropism for the human liver, developing animal models for preclinical screening of vaccine candidates is extremely challenging. To date, there are only a few reports regarding the use of humanized mouse models for the evaluation of the immunogenic properties of viral antigens.MethodsPreviously we showed that a Nicotiana benthamiana-produced HBV-S/preS116-42 antigen elicited strong HBV-specific immune responses in BALB/c mice. In the current study, we used immunodeficient NOD.Cg-Prkdcscid Il2rgtm1Wjl/SzJ (NSG) mice as recipients of human peripheral blood mononuclear cells (hPBMCs), to evaluate the immunogenicity of the recently developed chimeric HBV immunogen produced in CRISPR/Cas9-edited N. benthamiana, under more “humanized” conditions.ResultsAnalysis of the immune response in NSG mice immunized with the chimeric antigen demonstrated induction of virus infection-neutralizing antibodies, indicating activation of antigen-specific B cells.DiscussionThe ability of hPBMCs-engrafted NSG mice to mount specific humoral immune responses after immunization with viral antigens supports this animal model as a promising tool for pre-clinical evaluation of human vaccine antigens.